Suzanne Lacy between Kaprow and Chicago: Pedagogy and Performance. Issue 4 (December 2021) - Jones, Amelia
Abstract : Social practice and dematerialization are often cited as the most radical innovations in Euro-American contemporary art since the late 1960s, but rarely have historians acknowledged the crucial role of experimental pedagogy in this shift of art towards performance, conceptualism, and activism. The practice of Los Angeles–based performance artist Suzanne Lacy radically extended the ideas of her teachers and mentors Allan Kaprow and Judy Chicago into revised structures of artmaking towards activist social practice performances driven by conceptual, political, and embodied concerns.